OIKUMENE DAN RELASI SOSIAL : Membangun Perjumpaan Sejati Agama-Agama di Maluku Dalam Perspektif Etika Kristiani - Fatlolon, Costantinus (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2015)
This article presents a discourse on oecumene which is not restricted to “ecclesiastical oecumene”, but which intends to submit its metamorphosis into “inter-religious oecumene”, as a result of the phenomenon of the outset of the awareness of global ecumenism. The basic supposition of the article is that the “Oecumene between Churches” now constitute a real meeting-point of “inter-religious oecumene” in the Moluccas, when based on global ethics. In this way, various religions can live and cooperate in a sincere way, in peace and free from any intimidation or coercion for the sake of universal humanism. This article is also meant to be a critical reflection on the Decree Unitatis Redintegratio from the viewpoint of christian ethics.